Instrumentasi Viralitas Pada Konten Digital Marketing - Migotuwio, Namuri; Giovanni, Talitha Athaya; Prayogi, Rendy (Riset Sinergi Indonesia (RISINDO), 2025)
This research is motivated by the importance of the vitality of digital marketing content in optimizing promotion and advertising processes, which has been proven to increase sales. Along with the rising use of social media, the production of digital marketing videos has also grown significantly. This study aims to formulate visual instruments in digital marketing video content to achieve an optimal level of virality. The research method employed is qualitative, utilizing content analysis techniques on three advertisements: Marjan’s